Weight-added software reliability test method - FAN HANYANG; MA JUN; XU FAN; WU HAIBO; YUAN HAILIN; NI MING; YUAN LU; ZHANG QINGBIN; WU XIAOCHEN; NING YUE; ZHAO NING; CHEN JUN; et al. (2021)
The invention discloses a weight-added software reliability test method. The method comprises the following steps: dividing a to-be-tested software system into a plurality of subsystems according to different functions or service modules, and determining the weight of each subsystem according to the characteristics of the subsystems; measuring to obtain the severity of the fault, and determining the weight of the fault; and substituting the weight of each subsystem and the weight of the fault into a reliability calculation formula for calculation to obtain calculation results of all the subsystems, and integrating the calculation results of all the subsystems to obtain reliability evaluation of the software system to be tested. Compared with the prior art, the software test method providedby the invention makes up the problem of insufficient consideration of the influence of the weight factor in the current method, so that the reliability of the software test result is higher. 本发明公开了一种添加权重的软件可靠性测试方法。包括：将待测的软件